Effects of eight weeks of exercise training and orlistat therapy on body composition and maximal exercise capacity in obese females - Ozcelik, O; Dogan, H; Kelestimur, H (W B Saunders Co Ltd, 2006)
A comparative assessment was made of the short-term effects of orlistat therapy and exercise training on body composition and aerobic fitness in obese females. A total of 24 obese patients were enrolled in to the study; 12 received orlistat therapy (DO) and 12 participated in a regular aerobic exercise-training programme (DE). All patients were on hypocaloric diets. Each patient performed three incremental ramp exercise tests (one at Week 0, one at the end of Week 4 and one at the end of Week 8) to exhaustion using an electromagnetically braked cycle ergometer to determine their anaerobic threshold and maximal exercise (W-max) capacity. Patients in the DE group performed continuous exercise at a work rate that corresponded to the anaerobic threshold. Weight toss and toss of fat mass after 8 weeks were -6.4% (P= 0.002) and -13.4% (DE) vs -5.8% (P=0.002) and -6.4% (P= 0.008) (DO), respectively. Wmax capacity was 90.8 +/- 5 W (basal) vs 92.9 +/- 5 W (Week 4, P= 0.1) and 100.4 +/- 6 W (Week 8, 10.5%, P= 0.04) in the DO group, and 96.2 +/- 6 W (basal) vs 129.1 +/- 4 W (Week 4, 34. 1 %, P= 0.002) and 137.5 +/- 5 W (Week 8, 42.9%, P= 0.002) in the DE group. Despite similar decreases in body weight in both groups, patients in the DE group achieved a markedly higher level of Wmax, reflecting a better improvement in cardiopulmonary fitness, compared with patients in the DO group. Considering the improvement of aerobic fitness in the short term, an aerobic exercise-training programme should be considered for sedentary obese patients to improve their aerobic fitness and thereby reduce the negative outcomes of obesity. (c) 2005 The Royal Institute of Public Health. Published by Elsevier Ltd. All rights reserved.
Keywords: obesity; orlistat; weight loss; aerobic exercise